The Tudor-domain protein TDRD7, mutated in congenital cataract, controls the heat shock protein HSPB1 (HSP27) and lens fiber cell morphology. (18th May 2020) - Barnum, Carrie E; Al Saai, Salma; Patel, Shaili D; Cheng, Catherine; Anand, Deepti; Xu, Xiaolu; Dash, Soma; Siddam, Archana D; Glazewski, Lisa; Paglione, Emily; Polson, Shawn W; Chuma, Shinichiro; et al.
Abstract: Mutations of the RNA granule component TDRD7 (OMIM: 611258) cause pediatric cataract. We applied an integrated approach to uncover the molecular pathology of cataract in Tdrd7−/− mice. Early postnatal Tdrd7−/− animals precipitously develop cataract suggesting a global-level breakdown/misregulation of key cellular processes. High-throughput RNA sequencing integrated with iSyTE-bioinformatics analysis identified the molecular chaperone and cytoskeletal modulator, HSPB1, among high-priority downregulated candidates in Tdrd7−/− lens. A protein fluorescence two-dimensional difference in-gel electrophoresis (2D-DIGE)-coupled mass spectrometry screen also identified HSPB1 downregulation, offering independent support for its importance to Tdrd7−/− cataractogenesis. Lens fiber cells normally undergo nuclear degradation for transparency, posing a challenge: how is their cell morphology, also critical for transparency, controlled post-nuclear degradation? HSPB1 functions in cytoskeletal maintenance, and its reduction in Tdrd7−/− lens precedes cataract, suggesting cytoskeletal defects may contribute to Tdrd7−/− cataract. In agreement, scanning electron microscopy (SEM) revealed abnormal fiber cell morphology in Tdrd7−/− lenses. Further, abnormal phalloidin and wheat germ agglutinin (WGA) staining of Tdrd7−/− fiber cells, particularly those exhibiting nuclear degradation, reveals distinct regulatory mechanisms control F-actin cytoskeletal and/or membrane maintenance in post-organelle degradation maturation stage fiber cells. Indeed, RNA immunoprecipitation identified Hspb1 mRNA in wild-type lens lysate TDRD7-pulldowns, and single-molecule RNA imaging showed co-localization of TDRD7 protein with cytoplasmic Hspb1 mRNA in differentiating fiber cells, suggesting that TDRD7–ribonucleoprotein complexes may be involved in optimal buildup of key factors. Finally, Hspb1 knockdown in Xenopus causes eye/lens defects. Together, these data uncover TDRD7's novel upstream role in elevation of stress-responsive chaperones for cytoskeletal maintenance in post-nuclear degradation lens fiber cells, perturbation of which causes early-onset cataracts.